2001
DOI: 10.1097/00002508-200112000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Functional Disability in Chronic Pediatric Pain

Abstract: The implications for treatment of chronic pain in children are discussed with an emphasis on greater attention to developmental issues and their relation to coping, emotional functioning, and disability in pediatric pain. Further research examining differences in coping and disability between different pediatric pain groups is also warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
217
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 312 publications
(242 citation statements)
references
References 38 publications
21
217
0
4
Order By: Relevance
“…Adolescence is a period of emotional vulnerability and adjustment, reflected in increased risk for depression and other mental health conditions [49]. Indeed, children and adolescents with chronic pain have higher rates of depression than healthy peers, which may negatively impact both pain [25] and function [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescence is a period of emotional vulnerability and adjustment, reflected in increased risk for depression and other mental health conditions [49]. Indeed, children and adolescents with chronic pain have higher rates of depression than healthy peers, which may negatively impact both pain [25] and function [21].…”
Section: Discussionmentioning
confidence: 99%
“…Among children/adolescents, chronic pain is associated with several negative outcomes such as disability, depression, and poor social and school functioning [4,12,13,21,22,27,32,33,34,36].…”
Section: Introductionmentioning
confidence: 99%
“…The Children's Depression Inventory (CDI) is a validated and widely used measure of depressive symptoms in children and adolescents (17,18) and is frequently used to assess depressive symptoms in pediatric pain populations (4,5,19). For each item, adolescents choose 1 of 3 responses, representing varying symptom levels that best describe their symptoms for the past 2 weeks.…”
Section: Adolescent Functioningmentioning
confidence: 99%
“…Despite the fact that the literature notes that chronic pain in children and adolescents causes school truancy, inability take part in physical activities, sleep disturbances and problems relating to people in the same age group (7,9,27) , these aspects were not identified in this study. Analysis of the accounts showed that children and adolescents kept a social support network through their school friends, neighbors and family members, who helped them have a life that is closer to normality.…”
Section: Discussionmentioning
confidence: 90%
“…Many children and adolescents with chronic diseases and/or in the end-of-life phase live with pain daily, in addition to other signs and symptoms, such as: fatigue, dyspnea, anorexia, nausea, vomiting, insomnia, anxiety, despair, frustration and impotence when managing daily situations (7)(8)(9) .…”
Section: Introductionmentioning
confidence: 99%